2022
DOI: 10.3390/molecules27206916
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Insecticidal Effect and Interface Behavior of Nicotine Hydrochloride Solution by a Vesicle Surfactant

Abstract: Nicotine hydrochloride (NCT) has a good control effect on hemiptera pests, but its poor interfacial behavior on the hydrophobic leaf leads to few practical applications. In this study, a vesicle solution by the eco-friendly surfactant, sodium diisooctyl succinate sulfonate (AOT), was prepared as the pesticide carrier for NCT. The physical chemical properties of NCT-loaded AOT vesicles (NCT/AOT) were investigated by techniques such as dynamic light scattering (DLS), small-angle X-ray scattering (SAXS), and cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…27,28 Moreover, the contact angle of a water droplet on the AOT vesicle-modified gold electrode (34.9°) was much lower than that on the bare gold electrode (72.5°), which indicated that the modified vesicle layer made the electrode more hydrophilic (Figure S2). 31 Therefore, the AOT vesicles could be easily assembled on the surface of the gold electrode to obtain an AOT vesicle-modified microenvironment. Vesicle-Modified Microenvironment-Amplified Luminol ECL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27,28 Moreover, the contact angle of a water droplet on the AOT vesicle-modified gold electrode (34.9°) was much lower than that on the bare gold electrode (72.5°), which indicated that the modified vesicle layer made the electrode more hydrophilic (Figure S2). 31 Therefore, the AOT vesicles could be easily assembled on the surface of the gold electrode to obtain an AOT vesicle-modified microenvironment. Vesicle-Modified Microenvironment-Amplified Luminol ECL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, a gold electrode was immersed in the AOT vesicle solution for 10 min to obtain the AOT vesicle-modified gold electrode. Quartz crystal microbalance with dissipation monitoring (QCM-D) and contact angle measurements were used to investigate the self-assembly behavior of AOT vesicles on the surface of the gold electrode. ,, QCM-D measurement can study the adsorption of modifiers on the electrode using the piezoelectric properties of gold-plated quartz crystals. The basic resonant frequency F 0 is 5 MHz, and the adsorption of surfactants leads to a decrease in the frequency F .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…nisms of Target Compounds IIAa−f and IIBa−f. In the process of insecticide application, surfactant, 35 structural modification, 36 and water-based nanocarrier agents 37 have aided drug design in the promotion of pesticide aqueous solubility, resulting in the enhancement of insecticidal efficiency. Hence, the promotion of compound aqueous solubility on the basis of a structural modification strategy is worth conducting in this work.…”
Section: Design Strategy Based On πmentioning
confidence: 99%